Oral health status and treatment needs of children and young adults attending a day centre for individuals with special health care needs - Akindayomi Yinka; Oredugba Folakemi A (BMC, 2008)
Abstract Background The oral health condition of individuals with special health care needs have been reported in literature to be influenced by various sociodemographic factors, including living conditions and severity of impairment. This study was carried out to determine the oral health status and treatment needs of children and young adults attending a day institution for those with special needs. Methods This study was carried out as part of an oral health screening program organized by the institution and consent was obtained from parents and guardians before the screening. All information was supplied by the parents during the screening using a questionnaire completed by the dentist. Oral examination was carried out on all consenting subjects in attendance on the days of screening in the school clinic with parents and teachers in attendance, using standard World Health Organisation oral health indices to assess dental caries, oral hygiene status, malocclusion and other oral health parameters. Results Fifty-four subjects aged 3-26 years (mean 12.28 ± 6.82 years) and comprising 72.2% males and 27.8% females participated in the study. Over 90% were from parents of high and middle level educational background. Thirty-six (66.7%) were caries free, with a mean dmft score of 0.7 ± 1.77 and mean DMFT score of 0.4 ± 1.44 with no significant difference across gender (p = 0.5) and parents' educational status (p = 0.43). The mean OHI-S of the total population in this study was 1.36 ± 0.16. Females had a mean score of 0.88 ± 1.10 while males had a mean score of 1.55 ± 1.24 with no significant difference (p = 0.6). Twenty-five (46.3%) had good oral hygiene, 17 (31.5%) had fair oral hygiene and 12 (22.2%) had poor oral hygiene, with no significant difference across gender (p = 1.11) and age groups (p = 0.07). Fifteen (27.8%) had gingivitis with no significant difference across age groups (p = 0.17). Forty-five (83.3%) had Angle's class I malocclusion, 6(11.1%) class II and 3 (5.6%) class III. Chronologic enamel hypoplasia was found in 9 (16.7%) of the total population. Up to 53.7% of the total population will require oral prophylaxis, 33.3% required restorations on their posterior teeth and 12.9% required veneers for labial facing of hypoplastic enamel. Conclusion The subjects in this study had a high prevalence of dental caries and need for restorative care. They would benefit from parental education on diet modification, improvement of oral hygiene practices and regular dental visits.